Lec 34 16 3
Lec 34 16 3
Lec 34 16 3
Peter A. Perry
University of Kentucky
Reminders
Review
Review
Review
{( x, y) : x > 1} {( x, y) : x2 + y2 ≤ 4} {( x, y) : x2 + y2 > 4}
What is Z b
d
F (t) dt ?
a dt
What is Z b
d
F (t) dt ?
a dt
Answer: F (b) − F ( a)
y y y
x x x
A B C
y
At left is the contour plot for a function
f whose gradient is continuous.
90
80 Compute the following:
70
60
50
40
30
y
At left is the contour plot for a function
f whose gradient is continuous.
90
80 Compute the following:
70
• C ∇ f · dr
R
C1 60
50 1
40
30
y
At left is the contour plot for a function
f whose gradient is continuous.
90
C2 80 Compute the following:
70
• C ∇ f · dr
R
C1 60
50 1
40
• C ∇ f · dr
R
30 2
y
At left is the contour plot for a function
f whose gradient is continuous.
90
C2 80 Compute the following:
70
• C ∇ f · dr
R
C1 60
50 1
40
• C ∇ f · dr
R
30 2
y
At left is the contour plot for a function
f whose gradient is continuous.
90
C2 80 Compute the following:
70
• C ∇ f · dr
R
C1 60
50 1
40
• C ∇ f · dr
R
30 2
R
Definition A line integral C F · dr is independent of path in a domain D f
Z Z
F · dr = F · dr
C1 C2
for any two paths C1 and C2 that have the same initial and terminal points.
R
Theorem The integral C F · dr is independent of path for all paths in a
R
domain D if and only if C F · dr = 0 for every closed path in D.
P Q
{( x, y) : 1 ≤ x2 + y2 ≤ 2} {( x, y) : ( x, y) 6= (0, 0)}
{( x, y) : x2 + y2 ≤ 4}
∂P ∂ ∂f ∂2 f
= =
∂y ∂y ∂x ∂y∂x
∂P ∂ ∂f ∂2 f ∂Q ∂ ∂f ∂2 f
= = = =
∂y ∂y ∂x ∂y∂x ∂x ∂x ∂y ∂x∂y
∂P ∂ ∂f ∂2 f ∂Q ∂ ∂f ∂2 f
= = = =
∂y ∂y ∂x ∂y∂x ∂x ∂x ∂y ∂x∂y
∂P ∂Q
=
∂y ∂x
−y x
F( x, y) = i+ 2 j
x 2 + y2 x + y2 1 Does F satisfy the “conservative vector
2 field” condition?
1 2 Suppose
R C is the circle x2 + y2 = 1. What
is C F · dr for the vector field shown?
0
3 Is the domain
−1
{( x, y) : x2 + y2 6= 0}
−2 simply connected?
−2 −1 0 1 2
∂f
1 = y2 − 2x so taking antiderivatives in x
∂x
f ( x, y) = y2 x − x2 + C (y)
where C (y) is a constant that may depend on y
∂f
1 = y2 − 2x so taking antiderivatives in x
∂x
f ( x, y) = y2 x − x2 + C (y)
where C (y) is a constant that may depend on y
∂f
2 From the answer we found in step 1, = 2xy + C 0 (y) = 2xy so C 0 (y) = 0
∂y
∂f
1 = y2 − 2x so taking antiderivatives in x
∂x
f ( x, y) = y2 x − x2 + C (y)
where C (y) is a constant that may depend on y
∂f
2 From the answer we found in step 1, = 2xy + C 0 (y) = 2xy so C 0 (y) = 0
∂y
3 Finally, f ( x, y) = xy2 − x2 + C
F( x, y) = (1 + xy)e xy i + x2 e xy j
C : r(t) = cos ti + 2 sin tj, 0 ≤ t ≤ π/2